1981
DOI: 10.1111/j.1365-2478.1981.tb01015.x
|View full text |Cite
|
Sign up to set email alerts
|

The Offset System of Electrical Resistivity Sounding and Its Use With a Multicore Cable*†

Abstract: One of the most troublesome problems in resistivity sounding is caused by the spurious effects of near‐surface lateral resistivity variations. It has been found that the effects can be strongly reduced by measuring earth resistances at two electrode array positions such that in one position the lateral effect is a positive contribution to the total measured signal and in the other the contribution is negative. The subsequent combination of the two measurements virtually eliminates the lateral effect. The same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
1
5

Year Published

1986
1986
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(93 citation statements)
references
References 13 publications
1
86
1
5
Order By: Relevance
“…The problem, and one common to all electrode arrays, is that lateral near-surface conductivity inhomogeneities occurring near an electrode cause large effects attributable to variations in the vertical distribution of conductivity directly below the center of the array. To overcome this problem, various authors have suggested five electrode arrays to spatiaUy average out these lateral effects (Barker, 1981). For the induced polarization or spectral resistivity techniques, the transmitter generates a broadband signal either in the time domain or at discrete frequencies up to about I kHz.…”
Section: Inducedmentioning
confidence: 99%
“…The problem, and one common to all electrode arrays, is that lateral near-surface conductivity inhomogeneities occurring near an electrode cause large effects attributable to variations in the vertical distribution of conductivity directly below the center of the array. To overcome this problem, various authors have suggested five electrode arrays to spatiaUy average out these lateral effects (Barker, 1981). For the induced polarization or spectral resistivity techniques, the transmitter generates a broadband signal either in the time domain or at discrete frequencies up to about I kHz.…”
Section: Inducedmentioning
confidence: 99%
“…Improvement in resistivity methods using multi-electrode arrays has led to an important development in electrical imaging for subsurface surveys (Barker 1978;Griffiths and Turnbull 1985;Griffiths et al 1990;Barker 1992;Griffiths and Barker 1993). Such surveys are usually carried out using a large number of electrodes connected through a multi-core cable.…”
Section: Electrical Resistivity Imaging (Eri) Methodsmentioning
confidence: 99%
“…Obire et al (2008) show that fertilizer introduction to the land has a negative impact on the quality of groundwater. In conjunction with subsurface investigation, some pioneering work using the geoelectrical resistivity imaging technique was carried out by Barker (1981), Overmeeren van and Ritsema (1988), Griffiths et al (1990), Noel and Walker (1990), Griffiths and Barker (1993). The usefulness of this method for solving a number of geo-environmental problems has been shown by Reynolds (1997), Loke (1999), Abdul Nassir et al (2000) and Baharuddin et al (2009), with different case studies.…”
Section: Introductionmentioning
confidence: 99%